PROJECT-BASED LEARNING WITH POP-UP BOOKS: IMPACT ON WRITING AND LEARNING OUTCOMES - Nabila, Shafwah; Hadiansah, Dede; Khoimatun (Yayasan Amanah Nur Aman, 2025)
This research is motivated by the low learning outcomes of students in Indonesian language learning, particularly in writing short stories. Several factors contribute to this issue, including students’ limited understanding of short story writing, their lack of comprehension of intrinsic story elements, and their low writing skills. The purpose of this study is to examine the effect of the Project-Based Learning (PBL) model using pop-up book media on students’ short story writing skills and learning outcomes. The research employed a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of two classes: Class IV A as the experimental class, which received instruction through the PBL model and pop-up book media, and Class IV B as the control class, which received conventional instruction. Data collection techniques included a short story writing test and a learning achievement test in the form of multiple-choice and essay items. The results showed that the average score of short story writing skills in the experimental class increased from a pre-test score of 64.8 to a post-test score of 82.4, while the control class increased from 63.2 to 71.5. Regarding learning outcomes, the average post-test score of the experimental class was 84.6, compared to 73.8 in the control class. A t-test indicated that there was a significant difference between the experimental and control classes, both in short story writing skills and in learning outcomes. Thus, the use of the Project-Based Learning model assisted by pop-up book media was proven to effectively improve the short story writing skills and learning outcomes of fourth-grade elementary school students